Screening, Identification and Optimization of Biocontrol Conditions for Antagonistic Bacteria of Aspergillus niger - Xiaoyu XU; Tian LI; Xuewei SHI; Bin WANG (Shipin gongye ke-ji, 2022)
In order to screen for antagonistic bacteria with good inhibitory effect on black fungal disease in grape storage, in this study, strains with strong inhibitory effect on Aspergillus niger, which causes mycorrhizal lesions in grapes after harvest, were screened from soil by plate dilution method, identified using a combination of morphology and molecular biology, and optimized their growth and control conditions using single-factor and orthogonal tests. The results showed that 14 strains of bacteria with inhibitory effect on A.niger were isolated from vineyard soil in Xinjiang, among which, strain G8 had the best inhibitory effect on A.niger. The bacterium G8, which can antagonise A. niger, was identified as Bacillus siamensis. The optimum conditions for Bacillus siamensis G8 were: 3% inoculum, initial pH7, incubation temperature of 33 ℃, shaking speed of 160 r/min, and incubation time of 33 h. The inhibition diameter reached 28.79 mm under these conditions. The results of the study will provide theoretical basis for the application of antagonistic bacteria in the biological control of A. niger after grape harvest.